2021
DOI: 10.1002/ep.13629
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of methane emission from landfills using machine learning models

Abstract: Modeling the methane emission is challenging due to the heterogeneity of solid waste characteristics and different chemical and physical reactions leading to methane generation. This study focused on monitoring the methane generation from landfills and modeling methane emission using machine learning techniques. Hence, two pilot landfills were constructed with a total capacity of 9327 tons of municipal solid waste. The temperature, methane, and leachate generation from the pilot landfills were measured for 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The waste landfill has become the most critical waste disposal method in most countries because of its large-scale operation and simple management (Mehrdad et al 2021 ). However, landfills also present problems with siting, leachate, and odors (Abunama et al 2019 ; Mohsin et al 2022 ; Xu et al 2022 ).…”
Section: Illegal Dumping and Waste Disposalmentioning
confidence: 99%
“…The waste landfill has become the most critical waste disposal method in most countries because of its large-scale operation and simple management (Mehrdad et al 2021 ). However, landfills also present problems with siting, leachate, and odors (Abunama et al 2019 ; Mohsin et al 2022 ; Xu et al 2022 ).…”
Section: Illegal Dumping and Waste Disposalmentioning
confidence: 99%
“…With the rise in artificial intelligence techniques, much research on carbon price prediction based on artificial intelligence methods has emerged. 18 Owing to their advantages in solving large-scale and complicated nonlinear problems, they have been favored by many scholars. 19 For example, Sun and Huang utilized an optimized backpropagation (BP) neural network model to predict carbon prices.…”
Section: For Example Zhu Et Al Predicted the Development Trend Of Carbonmentioning
confidence: 99%
“…Kumar et al (2018) applied it to the prediction of the production rate of plastic waste, and found that the prediction result of SVM (R 2 0.74) is better than RF (R 2 0.66) and lower than artificial neural network (ANN) (R 2 0.75). Mehrdad et al (2021) argued that SVM was superior to both the adaptive neuro-fuzzy inference system and artificial neural network models in predicting methane generation.…”
Section: Support Vector Regressionmentioning
confidence: 99%
“…This model is widely used in waste management because of its strong fault-tolerant ability to describe the complex relationship between variables in a multivariate system. (Abbasi and El Hanandeh, 2016;Mehrdad et al, 2021;Nguyen et al, 2021;Niu et al, 2021). The deep neural network is a branch of ANN based on a perceptron model.…”
Section: Artificial Neural Networkmentioning
confidence: 99%